2011
DOI: 10.1097/fpc.0b013e32833ea085
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of the CYP3A5*1 and CYP3A5*3 alleles on pre-dose concentrations of two tacrolimus formulations

Abstract: This study provides further evidence that the CYP3A5*1/*3 polymorphism significantly impacts Tac pharmacokinetics. Moreover, we show for the first time a pharmacogenetic effect on two different Tac formulations, as Tac trough levels of *3/*3 patients declined significantly after conversion to identical A-Tac doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 0 publications
5
25
2
1
Order By: Relevance
“…In CYP3A5 pharmacogenetics, the daily dose was higher in CYP3A5 expressers than nonexpressers for both formulations. The AUC 0-24 , AUC [12][13][14][15][16][17][18][19][20][21][22][23][24] , and C 0 for Tac-QD, but not Tac-BID, were smaller, approximately 25%, 30%, and 35% respectively, in CYP3A5 expressers than nonexpressers. There were no differences in maximum blood concentration (C max ) and the observed time to reach the maximum blood concentration (T max ) (from 0 to 12 hours) between the two genotypes for each formulation.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…In CYP3A5 pharmacogenetics, the daily dose was higher in CYP3A5 expressers than nonexpressers for both formulations. The AUC 0-24 , AUC [12][13][14][15][16][17][18][19][20][21][22][23][24] , and C 0 for Tac-QD, but not Tac-BID, were smaller, approximately 25%, 30%, and 35% respectively, in CYP3A5 expressers than nonexpressers. There were no differences in maximum blood concentration (C max ) and the observed time to reach the maximum blood concentration (T max ) (from 0 to 12 hours) between the two genotypes for each formulation.…”
Section: Resultsmentioning
confidence: 83%
“…To date, two studies have showed the controversial impact of CYP3A5 polymorphisms on the pharmacokinetics of switching from Tac-BID to Tac-QD in stable renal transplant recipients (14,15). This study is the first to show the effect of CYP3A5 polymorphisms on the pharmacokinetics of Tac-QD in de novo renal transplant patients.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…CYP3A5 expressers) than in those with the CYP3A5*1/*1 genotype (CYP3A5 non-expressers) [19,27,36,61]. In contrast, two studies reported the opposite, that patients with the CYP3A5*3/*3 genotype (CYP3A5 non-expressers) were the ones who experienced the largest decrease in AUC 0-24 and/or C min following milligram-per-milligram-based conversion [32,38]. One study, which reported that conversion from Prograf Ò to Advagraf Ò resulted in a significant decrease in withinsubject variability in AUC 0-24 , found that this decrease was numerically greatest in patients with the CYP3A5*1 genotype (% CV down from 18.2 to 12.8 % on conversion in CYP3A5 expressers versus a decrease from 12.6 to 10.2 % on conversion in CYP3A5 non-expressers) [28].…”
Section: Xrmentioning
confidence: 94%
“…Factors in these traditional design studies reported to influence the pharmacokinetics of prolonged-release tacrolimus included patient CYP3A5 genotype status [17,19,27,28,32,36,38,61], age [51], race [57] and time after transplantation [17]. These same factors were also reported to be influential when immediate-release tacrolimus was administered twice daily [3].…”
Section: Xrmentioning
confidence: 99%